A method for producing high-purity anhydrous manganese acetate
By controlling the free acid content and adopting double cone drying technology, the problems of unqualified insoluble substances in water and uneven product quality in the production of anhydrous manganese acetate are solved, and high purity and high efficiency production are achieved.
Patent Information
- Application Number
- CN202411519008.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-10-29
AI Technical Summary
In the existing production methods for anhydrous manganese acetate, the insoluble substances in the water are unqualified and there is obvious turbidity, the product is prone to clumping, and the quality is uneven.
By controlling the free acid content during synthesis and crystallization, the drying method is carried out by double cone drying, the drying temperature and vacuum degree are controlled, the hydrolysis and oxidation of manganese acetate are inhibited, and the purity and quality uniformity of the product are improved.
The production of anhydrous manganese acetate is achieved with high purity (≥99.9%), which solves the problems of unqualified insoluble substances in water and uneven product quality, and improves production efficiency and product quality.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to a method for producing high-purity anhydrous manganese acetate, and belongs to the technical field of chemical industry. Background Art
[0002] Manganese acetate is a very important organic manganese compound with a wide range of applications. It can be widely used as a catalyst for different chemical reactions, including oxidation reactions (acetaldehyde oxidation catalysis, xylene high-temperature oxidation catalyst, fiber dyeing oxidation catalyst, etc.), vinyl ester complex polymerization reaction (used as a catalyst for ester exchange reaction, the dosage in the production of polyester resin is about 0.01%~0.05%), and can also be used for leather processing, dyeing mordant, coating and paint drying agent, and also used in fertilizers, food and feed additives.
[0003] Due to market demand, when the tetrahydrate manganese acetate was further processed into anhydrous manganese acetate, it was found that the water insoluble matter of the product was unqualified and the product was obviously turbid. Anhydrous manganese acetate is currently produced in a relatively small amount on the market. Although the water insoluble matter of anhydrous manganese acetate produced by the prior art meets the product qualification requirements and the solution can be in a slightly turbid state, it still cannot meet the needs of customers; at the same time, the material is easy to agglomerate and the quality is uneven. Summary of the invention
[0004] To address at least one of the problems existing in the prior art, the present invention provides a method for producing high-purity anhydrous manganese acetate.
[0005] Through experiments, it was found that the main reason for the unqualified insoluble matter in water of anhydrous manganese acetate is that a small amount of manganese acetate is easily decomposed into manganese oxide or manganese hydroxide during the treatment process. Although the agglomeration of materials can be solved by crushing, the whole production process is cumbersome, which reduces the production efficiency. In view of the problems reviewed above, the existing technology is improved and the problems are solved through key points: first, how to inhibit the decomposition of manganese acetate can fundamentally solve the problem of unqualified insoluble matter in water; secondly, how to make the produced anhydrous manganese acetate particles uniform and of uniform quality, thereby improving production efficiency and reducing the labor of workers; finally, the purity of anhydrous manganese acetate is further optimized to make the purity ≥99.9%.
[0006] In order to achieve the above object, the present invention adopts the following technical scheme: a method for producing high-purity anhydrous manganese acetate, comprising the following production steps:
[0007] (1) Synthesis: Glacial acetic acid is diluted with pure water, and manganese flakes are added to carry out a synthesis reaction. The mass ratio of manganese flakes to glacial acetic acid is controlled at 1:2.95-3.48. The free acid content during the synthesis process is controlled at 6.9-11.4%, which can inhibit the hydrolysis of manganese acetate to manganese hydroxide and facilitate subsequent crystallization. The synthesis temperature is ≤100°C, the synthesis time is ≥3h, and the solution is clarified by filtration to remove mechanical impurities to obtain a synthetic liquid.
[0008] (2) Concentrating: concentrating the synthetic liquid at a temperature ≤ 110° C. to obtain a concentrated liquid;
[0009] (3) Crystallization: The concentrated solution is cooled to 35-40° C. for crystallization. During the crystallization process, the free acid content is controlled at 7.4-11.8%. After the crystallization is completed, dehydration is performed to obtain manganese acetate crystals.
[0010] (4) Drying: The manganese acetate crystals are dried using a double cone drying method, the drying vacuum degree is ≤-0.090 MPa, the drying temperature is gradually increased from 60°C to 90°C, and then the drying is carried out by heat preservation to obtain anhydrous manganese acetate with a content of ≥99.9%.
[0011] Preferably, in step (1), the mass ratio of manganese flakes to glacial acetic acid is controlled at 1:2.95-3.38, and the free acid content during the synthesis process is controlled at 6.9-10.5%.
[0012] Preferably, in step (1), the mass ratio of manganese flakes to glacial acetic acid is controlled at 1:3.06, and the free acid content is controlled at 7.8%.
[0013] Preferably, in step (2), the concentrate is performed until the Bé specific gravity is 30-40° Bé.
[0014] Preferably, in step (2), the concentrate is performed until the Bé gravity is 37-40° Bé.
[0015] Preferably, in step (3), the free acid content is controlled at 7.4-11.4%.
[0016] Preferably, in step (3), the free acid content is controlled at 8.1%.
[0017] Preferably, in step (3), the crystallization endpoint temperature is 40°C.
[0018] Preferably, in step (3), the dehydration time is 10 to 20 min / machine.
[0019] Preferably, in step (4), the temperature rise rate is 10° C. / h.
[0020] Preferably, in step (4), the drying is carried out for 1 to 2 hours.
[0021] The invention has the following beneficial effects: 1. The production method of the invention controls the content of free acid in the synthesis and crystallization processes, and controls the drying temperature to inhibit the non-melting of manganese acetate, thereby effectively inhibiting the hydrolysis and oxidation of manganese acetate, so that the purity of anhydrous manganese acetate is ≥99.9%, meeting the standard of analytical purity; 2. The product does not need to be crushed. The production method of the invention uses a double-cone drying method to dry the material in a continuous turning process, which can make the particle size uniform and the quality uniform; 3. Compared with the existing production method, the production method of the invention uses double-cone drying, which also greatly shortens the drying time, and the product quality is significantly improved. DETAILED DESCRIPTION
[0022] The following is a clear and complete description of the technical solutions in the implementation of the present invention. The described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. If the specific conditions are not specified in the embodiments, they are carried out according to the normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents, instruments, and components used, they are all conventional products that can be purchased commercially.
[0023] 1. Effect of free acid content on the quality of anhydrous manganese acetate products
[0024] Example 1 to Example 5 and Comparative Example 1
[0025] The glacial acetic acid was diluted with pure water to acetic acid solutions with mass fractions of 27.5%, 28.5%, 29.5%, 30.5%, 32.5%, and 33.5%, and 260 g of manganese flakes and 2700 g of acetic acid solution were added to carry out synthesis reactions. The corresponding free acid contents in the synthesis process were controlled to be 5.9%, 6.9%, 7.8%, 8.7%, 10.5%, and 11.4%, and the synthesis temperatures were all ≤100°C and the synthesis times were all 4 hours. The mechanical impurities were removed by filtration to clarify the solution, and the obtained The synthetic liquid was concentrated at a temperature of ≤110°C, and the concentrated specific gravity was 38°Bé. It was then cooled and crystallized at a temperature of 35°C. The corresponding free acid content was controlled at 6-12% during the crystallization process. It was then dehydrated using a centrifuge for 15 minutes. It was then dried using a rotary evaporator to simulate the double-cone drying method of a double-cone dryer. The drying vacuum was -0.095MPa, and the drying temperature was increased from 60°C to 90°C at a rate of 10°C / h, and the product was kept warm and dried for 2 hours. The results are shown in Table 1.
[0026] Table 1 Effect of free acid content on the quality of anhydrous manganese acetate products
[0027]
[0028] Experiment shows: from embodiment 1 to embodiment 5 and comparative example 1 in table 1, the content of free acid in crystallization process is slightly higher than the free acid content of synthesis process, and the change of free acid content can affect the insoluble matter and content in solution. When the content of free acid in crystallization process is less than 7.4%, the free acid content in the corresponding synthesis process is less than 6.9%, and the insoluble matter content in water exceeds 0.01%, which is unqualified, and the solution is also slightly turbid, when the content of free acid in crystallization process is more than 11%, the free acid content in the corresponding synthesis process is more than 10.5%, and the insoluble matter in water is basically stable, which is 0.004%, and the solution is clarified. Therefore, the content of free acid in crystallization process is 7.4~11.8%, and the free acid content in the corresponding synthesis process is more preferably 6.9~11.4%, and the manganese acetate produced is of excellent quality, with a content of more than 99.9%, and the insoluble matter content in water in manganese acetate is less than 0.01%, which meets the standard of analytical purity, and the free acid content is too low, and manganese acetate is hydrolyzed into manganese hydroxide, which reduces the quality of manganese acetate product.
[0029] Therefore, in the present invention, the mass ratio of the synthetic raw material manganese flakes and acetic acid is preferably controlled to be 1:2.95-3.38. On this basis, the glacial acetic acid is excessive so that the content of the free acid in the synthesis process is preferably controlled to be 6.9-10.5%, so as to inhibit the hydrolysis of manganese acetate to manganese hydroxide, solve the problem that the excessive manganese flakes will cause a large amount of metallic manganese to be lost in the filtration process, thereby causing high consumption, and the manganese hydroxide is not easy to filter clean, and a filter aid needs to be added, so that the solid waste is not easy to handle, and the production operation is cumbersome and complicated. In the crystallization process, the content of the free acid is preferably controlled to be 7.4-11%. If the free acid content is low, acetic acid needs to be added. The purpose is to allow a small amount of free acid to adhere to the surface of the dehydrated manganese acetate, which is conducive to the anhydrous manganese acetate not being easy to hydrolyze oxygen during the drying process. If the free acid content is too high, it will cause adverse effects on environmental protection, energy consumption and efficiency.
[0030] 2. Effect of different drying methods on the quality of anhydrous manganese acetate products
[0031] Example 6 and Comparative Example 2
[0032] 260g manganese flakes and 2700g acetic acid solution with a mass fraction of 29.5% were added for synthesis reaction. The corresponding free acid content in the synthesis process was controlled to be 7.8%, the synthesis temperature was ≤100℃, the synthesis time was 4h, and then the mechanical impurities were removed by filtration to clarify the solution. The obtained synthetic solution was concentrated at a temperature of ≤110℃, and the concentrated specific gravity was 38°Bé. Then the temperature was lowered for crystallization, and the crystallization temperature was 35℃. The corresponding free acid content in the crystallization process was controlled to be 8.1%. Then it was dehydrated by centrifuge, and the dehydration time was 15min. Then it was divided into two parts and dried by double cone drying and oven drying as shown in Table 2, respectively. The vacuum degree of double cone drying was -0.095MPa, and the temperature of double cone drying and oven drying was increased from 60℃ to 90℃ at a rate of 10℃ / h, and the heat preservation and drying were carried out for 2h. The results are shown in Table 2.
[0033] Table 2 Effects of different drying methods on the quality of anhydrous manganese acetate products
[0034]
[0035] Experiments show that: from Example 6 and Comparative Example 2 in Table 2, it can be seen that when the oven drying method is used, manganese acetate is prone to melting, agglomeration, uneven particles, etc., resulting in unqualified water insoluble matter in manganese acetate, with a content greater than 0.0.2%; therefore, the present invention adopts double cone drying as the best drying method, which can dry the material in the process of continuous turning, avoid melting of manganese acetate, and make the particle size uniform and the quality uniform.
[0036] Experiments have shown that, in order to prevent manganese acetate from melting, if the oven drying temperature is set too low, the crystal water is not easy to remove, and if the temperature is a little higher, the bottom of the manganese acetate is easy to melt, and in the process of drying the material in the oven, it is found that the material is easy to form large lumps, and the material needs to be frequently turned and crushed to make the content of anhydrous manganese acetate reach the standard of analytical purity; therefore, the present invention changes the drying method to double cone drying, which can remove the crystal water and ensure that the manganese acetate will not melt during the drying process under vacuum conditions.
[0037] 3. Effect of Double Cone Drying Temperature and Vacuum Degree on the Quality of Anhydrous Manganese Acetate Products
[0038] Example 7 to Example 8 and Comparative Example 3 to Comparative Example 9
[0039] 260g of manganese flakes and 2700g of acetic acid solution with a mass fraction of 29.5% were added for synthesis reaction. The corresponding free acid content in the synthesis process was controlled to be 7.8%, the synthesis temperature was ≤100℃, the synthesis time was 4h, and then the mechanical impurities were removed by filtration to clarify the solution. The obtained synthetic liquid was concentrated at a temperature of ≤110℃, and the concentrated specific gravity was 38°Bé. Then the temperature was lowered for crystallization, and the crystallization temperature was 35℃. The corresponding free acid content in the crystallization process was controlled to be 8.1%. Then it was dehydrated by centrifuge, and the dehydration time was 15min. Then it was evenly divided into nine parts and dried by double cone drying method at different drying temperatures and vacuum conditions as shown in Table 3. The results are shown in Table 3.
[0040] Table 3 Effects of double cone drying temperature and vacuum degree on the quality of anhydrous manganese acetate products
[0041]
[0042] Experiments show that: from Example 7 to Example 8 and Comparative Example 3 to Comparative Example 9 in Table 3, it can be seen that the drying temperature is set in combination with the vacuum degree of the double cone drying equipment. The vacuum degree is high, and it is not easy to pull out water at 60°C. When the materials are gathered together, they are easy to melt. At this time, the materials will appear to be clumping and hanging on the wall, which makes it difficult to dry and reduces production efficiency; therefore, the present invention selects the drying vacuum degree to be controlled at ≤-0.090MPa. It is further found that under this vacuum degree, the drying temperature remains unchanged: when the temperature is high, the material has melting, hanging on the wall, and agglomeration, which affects the product quality. When the temperature is lowered, the removal rate of crystal water cannot be high, which also leads to reduced product quality. Moreover, with the loss of crystal water, the melting point of manganese acetate becomes larger, so the drying temperature can be gradually increased. The drying temperature is gradually increased and then kept warm: if the initial drying temperature is too high, the material will melt, hang on the wall, and agglomerate, which will affect the product quality; if the terminal drying temperature is too low, the crystal water cannot be removed at a low rate, resulting in reduced product quality; the drying vacuum degree needs to be controlled at ≤-0.090MPa. The present invention selects a double cone drying initial temperature of 60°C, gradually increases the temperature to a terminal temperature of 90°C, and obtains anhydrous manganese acetate with uniform particle size and uniform quality. Such a drying temperature can effectively remove the crystal water and attached water of manganese acetate, and can also inhibit the non-melting of manganese acetate, thereby solving the problem that manganese acetate is easily hydrolyzed into manganese hydroxide after melting, and then slowly oxidized into manganese oxide, which ultimately leads to the problem that the insoluble matter in the water of anhydrous manganese acetate is unqualified; the specific drying time is determined by the quality of the dried material.
[0043] 4. Effect of crystallization endpoint temperature on the quality of anhydrous manganese acetate products
[0044] Example 9 to Example 11 and Comparative Example 10 to Comparative Example 11
[0045] 260g manganese flakes and 2700g acetic acid solution with a mass fraction of 29.5% were added for synthesis reaction. The corresponding free acid content in the synthesis process was controlled to be 7.8%, the synthesis temperature was ≤100℃, the synthesis time was 4h, and then the mechanical impurities were removed by filtration to clarify the solution. The obtained synthetic solution was concentrated at a temperature of ≤110℃, and the concentrated specific gravity was 38°Bé. Then the temperature was lowered and crystallized. The crystallization temperatures were 30℃, 35℃, 40℃, and 45℃ as shown in Table 4. The corresponding free acid content in the crystallization process was controlled to be 8.1%. Then the product was dehydrated by centrifuge, and the dehydration time was 15min. Then the product was divided into 4 parts and dried by double cone drying method. The drying vacuum was -0.095MPa, and the drying temperature was increased from 60℃ to 90℃ at a rate of 10℃ / h. The product was kept warm and dried for a period of time, as shown in Table 4. The results are shown in Table 4.
[0046] Table 4 Effect of crystallization endpoint temperature on the quality of anhydrous manganese acetate product
[0047]
[0048] The experiment shows that: from Example 9 to Example 11 and Comparative Example 10 to Comparative Example 11 in Table 4, it can be seen that the crystallization endpoint temperature determines the water content of manganese acetate after dehydration, and the water content mainly refers to crystallization water. When the crystallization endpoint temperature is 35-40°C, the crystallization water of manganese acetate is close to the trihydrate state, which is more conducive to the drying of anhydrous manganese acetate, making it difficult to melt during the drying process, thereby causing hydrolysis and oxidation, and also improving the production efficiency of anhydrous manganese acetate. When the crystallization endpoint temperature is >40°C, it is easy to agglomerate during the dehydration process, which is difficult to operate and the yield is greatly reduced. When the crystallization endpoint temperature is <35°C, the material has a high water content, a long drying time, and is prone to melting during the drying process, and the yield is greatly reduced.
[0049] In addition, from synthesis to crystallization, the setting of process parameters is to lay the foundation for the drying process. A large number of experiments have found that once the dehydrated manganese acetate (manganese acetate with crystal water) melts during drying, it is very easy to hydrolyze and oxidize, resulting in the production of manganese hydroxide and manganese oxide, causing the quality of anhydrous manganese acetate to be unqualified.
[0050] Example 12
[0051] 260g of manganese flakes and 2700g of acetic acid solution with a mass fraction of 29.5% were added for synthesis reaction. The corresponding free acid content in the synthesis process was controlled to be 7.8%, the synthesis temperature was 95°C, the synthesis time was 4h, and then the mechanical impurities were removed by filtration to clarify the solution. The obtained synthetic solution was concentrated at a temperature of 105°C, and the concentrated specific gravity was 37°Bé. Then the temperature was lowered for crystallization, and the crystallization temperature was 35°C. The corresponding free acid content in the crystallization process was controlled to be 8.1%. Then, it was dehydrated by a centrifuge for 15min and dried by a double cone drying method. The vacuum degree of the double cone drying was -0.095MPa. The temperature of the double cone drying was increased from 60°C to 90°C at a rate of 10°C / h. The product was kept warm and dried for 2h to obtain a manganese acetate product with uniform particle size and uniform quality. The purity was 99.93%, the yield was 82.1%, the insoluble matter content in water was 0.007%, and the solution was clear.
[0052] Embodiment 13
[0053] 260g of manganese flakes and 2700g of acetic acid solution with a mass fraction of 29.5% were added for synthesis reaction. The corresponding free acid content in the synthesis process was controlled to be 7.8%, the synthesis temperature was 95°C, the synthesis time was 4h, and then the mechanical impurities were removed by filtration to clarify the solution. The obtained synthetic solution was concentrated at a temperature of 105°C, and the concentrated specific gravity was 39°Bé. Then the temperature was lowered for crystallization, and the crystallization temperature was 35°C. The corresponding free acid content in the crystallization process was controlled to be 8.1%. Then, it was dehydrated by a centrifuge for 15min and dried by a double cone drying method. The vacuum degree of the double cone drying was -0.095MPa. The temperature of the double cone drying was increased from 60°C to 90°C at a rate of 10°C / h. The product was kept warm and dried for 2h to obtain a manganese acetate product with uniform particle size and uniform quality. The purity was 99.94%, the yield was 82.4%, the insoluble matter content in water was 0.007%, and the solution was clear.
[0054] Embodiment 14
[0055] 260g of manganese flakes and 2700g of acetic acid solution with a mass fraction of 29.5% were added for synthesis reaction. The corresponding free acid content in the synthesis process was controlled to be 7.8%, the synthesis temperature was 95°C, the synthesis time was 4h, and then the mechanical impurities were removed by filtration to clarify the solution. The obtained synthetic solution was concentrated at a temperature of 105°C, and the concentrated specific gravity was 36°Bé. Then the temperature was lowered for crystallization, and the crystallization temperature was 35°C. The corresponding free acid content in the crystallization process was controlled to be 8.1%. Then, it was dehydrated by a centrifuge for 15min and dried by a double cone drying method. The vacuum degree of the double cone drying was -0.095MPa. The temperature of the double cone drying was increased from 60°C to 90°C at a rate of 10°C / h. The product was kept warm and dried for 2h to obtain a manganese acetate product with uniform particle size and uniform quality. The purity was 99.94%, the yield was 81.4%, the content of insoluble matter in water was 0.008%, and the solution was clear.
[0056] Embodiment 15
[0057] 260g of manganese flakes and 2700g of acetic acid solution with a mass fraction of 29.5% were added for synthesis reaction. The corresponding free acid content in the synthesis process was controlled to be 7.8%, the synthesis temperature was 95°C, the synthesis time was 4h, and then the mechanical impurities were removed by filtration to clarify the solution. The obtained synthetic solution was concentrated at a temperature of 105°C, and the concentrated specific gravity was 31°Bé. Then the temperature was lowered for crystallization, and the crystallization temperature was 35°C. The corresponding free acid content in the crystallization process was controlled to be 8.1%. Then, it was dehydrated by a centrifuge for 15min and dried by a double cone drying method. The vacuum degree of the double cone drying was -0.095MPa. The temperature of the double cone drying was increased from 60°C to 90°C at a rate of 10°C / h. The product was kept warm and dried for 2h to obtain a manganese acetate product with uniform particle size and uniform quality, a purity of 99.94%, a yield of 77.8%, a water insoluble content of 0.009%, and a clear solution.
[0058] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the present invention can be implemented in other specific forms without departing from the spirit and essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0059] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This narrative method of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment can also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A method for producing anhydrous manganese acetate, characterized in that: The production process includes the following steps: (1) Synthesis: dilute glacial acetic acid with pure water, add manganese flakes to carry out synthesis reaction, the mass ratio of manganese flakes to glacial acetic acid is controlled at 1:2.95~3.48, the free acid content during the synthesis process is controlled at 6.9~11.4%, the synthesis temperature is ≤100°C, the synthesis time is ≥3h, and then filter to obtain a synthetic liquid; (2) Concentrating: concentrating the synthetic liquid at a temperature ≤ 110° C. to obtain a concentrated liquid; (3) Crystallization: The concentrated solution is cooled to 35-40° C. for crystallization. During the crystallization process, the free acid content is controlled at 7.4-11.8%. After the crystallization is completed, dehydration is performed to obtain manganese acetate crystals. (4) Drying: The manganese acetate crystals are dried using a double cone drying method, the drying vacuum degree is ≤-0.090 MPa, the drying temperature is gradually increased from 60°C to 90°C, and then the drying is carried out by heat preservation to obtain anhydrous manganese acetate with a content of ≥99.9%.
2. The method for producing anhydrous manganese acetate according to claim 1, characterized in that: In step (4), the temperature rise rate is 10°C / h.
3. The method for producing anhydrous manganese acetate according to claim 1, characterized in that: In step (1), the mass ratio of manganese flakes to glacial acetic acid is controlled at 1:2.95-3.38, and the free acid content during the synthesis process is controlled at 6.9-10.5%.
4. The method for producing anhydrous manganese acetate according to claim 1 or 3, characterized in that: In step (1), the mass ratio of manganese flakes to glacial acetic acid is controlled at 1:3.06, and the free acid content is controlled at 7.8%.
5. The method for producing anhydrous manganese acetate according to claim 1, characterized in that: In step (3), in the crystallization step, the free acid content is controlled at 7.4-11.4%.
6. The method for producing anhydrous manganese acetate according to claim 1 or 5, characterized in that: In step (3), during the crystallization step, the free acid content is controlled at 8.1%.
7. The method for producing anhydrous manganese acetate according to claim 1, characterized in that: In step (2), the mixture is concentrated to a specific gravity of 30-40° Bé.
8. The method for producing anhydrous manganese acetate according to claim 1 or 7, characterized in that: In step (1), in the concentration step, the concentrate is performed until the specific gravity of the alcohol is 37-40° Bé.
9. The method for producing anhydrous manganese acetate according to claim 1, characterized in that: In step (2), the crystallization endpoint temperature is 40°C.
10. The method for producing anhydrous manganese acetate according to claim 1, characterized in that: In step (4), keep warm and dry for 1 to 2 hours.
Citation Information
Patent Citations
Efficient crystallization process for cobalt acetate
CN117658799A
Method for preparing manganese acetate
CN1626495A